2014
DOI: 10.1021/nl503756y
|View full text |Cite
|
Sign up to set email alerts
|

Gate-Tunable Resonant Tunneling in Double Bilayer Graphene Heterostructures

Abstract: Abstract:We demonstrate gate-tunable resonant tunneling and negative differential resistance in the interlayer current-voltage characteristics of rotationally aligned double bilayer graphene heterostructures separated by hexagonal boron-nitride (hBN) dielectric. An analysis of the heterostructure band alignment using individual layer densities, along with experimentally determined layer chemical potentials indicates that the resonance occurs when the energy bands of the two bilayer graphene are aligned. We dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
165
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(179 citation statements)
references
References 27 publications
13
165
1
Order By: Relevance
“…Thinner barrier devices show a finite linear tunnel current at low biases and a roughly exponential dependence of the low bias resistance with d, complying with standard quantum mechanical tunneling, in agreement with previous reports 9,12 . However, in relatively thicker barrier devices, we find signatures of Coulomb blockade and single electron tunneling events.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Thinner barrier devices show a finite linear tunnel current at low biases and a roughly exponential dependence of the low bias resistance with d, complying with standard quantum mechanical tunneling, in agreement with previous reports 9,12 . However, in relatively thicker barrier devices, we find signatures of Coulomb blockade and single electron tunneling events.…”
supporting
confidence: 91%
“…The voltage range probed is believed to be below the Fowler-Nordheim regime, where the barrier is essentially triangular, due to a very high applied bias 8 . In recent studies, NDR signatures were observed in single and bilayer graphene based heterostructures, which were attributed to resonant tunneling via momentum conservation when the energy bands of the top and bottom graphene layers were aligned 11,12 . However, we find sim-ilar I-V curves in simple M-I-M junctions here, albeit with peak to valley ratios lower than in graphene based devices.…”
mentioning
confidence: 99%
“…Resonate tunneling current and negative differential resistance (NDR) have been observed in graphene‐based heterostructure TFETs, including monolayer and bilayer graphene separated by BN25, 26, 27, 28, 29, 30 or TMDs 6, 31. However, due to the absence of a bandgap, graphene‐based TFETs are unable to obtain a high on/off ratio of the current.…”
Section: Introductionmentioning
confidence: 99%
“…2, 31, 32) and bilayer graphene (Refs. 33,34) as presented in the thesis have been observed in the time since this work began. Therefore, it is single-particle e ects that will be the focus of the thesis, and beyond this section many-body e ects will not be considered further.…”
Section: Many-body E Ects and Excitonic Condensatesmentioning
confidence: 83%